Audit Delay of Listed Companies On The IDX - Rani, Erma Hartika; Triani, Ni Nyoman Alit (Universitas Pendidikan Indonesia, 2021)
The purpose of this study is to examine the effect of company size, company age, profitability, leverage, and audit tenure on audit delay. The sample in this study is select with a purposive sampling method on the companies listed on the IDX in 2019, with a total sample of 581 companies. The method of analysis used multiple linear regressions. The result of this study indicates that company size and profitability negatively influenced audit delay. Meanwhile, the company age, leverage, and audit tenure did not affect audit delay.